2003
DOI: 10.1111/j.1365-2028.2003.00475.x
|View full text |Cite
|
Sign up to set email alerts
|

Phenology of figs in Budongo Forest Uganda and its importance for the chimpanzee diet

Abstract: This paper reports on the phenological patterns of figs in Budongo Forest, Uganda, and how it relates to chimpanzee food availability in different seasons. In addition, we analysed the dung of chimpanzees to understand the composition of fruits in their diet. The aim of our study was to assess Ficus phenology and how it affects chimpanzee diet. Fifteen species of figs were monitored for fruit (syconium) and leaf phenology between June 2000 and 2001. Ficus fruit production varied significantly between and withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 20 publications
4
46
0
1
Order By: Relevance
“…For instance, C-peptide concentrations of Kanyawara chimpanzees were particularly high when they consumed Ficus sur. This fig, rare at Kanyawara, produces large clusters of plump fruits and is noted as the dominant, and likely preferred, species consumed by another Ugandan chimpanzee community (Budongo: Emery Thompson, 2005b;Fawcett, 2000;Newton-Fisher, 1999;Tweheyo and Lye, 2003). While our examination focused on fruits as a category of high-quality foods, detailed, long-term C-peptide analysis could help elucidate the nutritional benefits of other items in the diverse chimpanzee diet, such as the ability of different fall-back foods to buffer seasonal fruit availability (Malenky et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, C-peptide concentrations of Kanyawara chimpanzees were particularly high when they consumed Ficus sur. This fig, rare at Kanyawara, produces large clusters of plump fruits and is noted as the dominant, and likely preferred, species consumed by another Ugandan chimpanzee community (Budongo: Emery Thompson, 2005b;Fawcett, 2000;Newton-Fisher, 1999;Tweheyo and Lye, 2003). While our examination focused on fruits as a category of high-quality foods, detailed, long-term C-peptide analysis could help elucidate the nutritional benefits of other items in the diverse chimpanzee diet, such as the ability of different fall-back foods to buffer seasonal fruit availability (Malenky et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…However, this proportion greatly depends on the population analyzed. Basabose (2002) reported 58% fruit consumption in the Kahuzi chimpanzee population (Pan t. schweinfurthii), whereas in the Democratic Republic of the Congo, for the same subspecies, Tweheyo and Obua (2001) and Tweheyo and Lye (2003) described 83% fruit ingestion at the Budongo Forest Reserve in Uganda. Other studies have reported 87% consumption of fruits and seeds for Pan t. troglodytes (Tutin and Fernández 1993) and 72% for Pan t. verus in Bossou (Sugiyama and Koman 1992), similar to the percentage reported for the Kibale Pan t. schweinfurthii (67%) (Wrangham et al 1991).…”
Section: Dietary Habits and Ecology Of The African Hominoideamentioning
confidence: 91%
“…5). In addition, figs were the most commonly eaten fruit in the chimpanzee diet at Bulindi [36], as at Sonso [40,56]. Riverine forests in Bulindi contained a higher density of fig trees (16.8 individuals ha -1 ) than many tropical forests [cf.…”
Section: Discussionmentioning
confidence: 99%
“…Members of the Moraceae produce fleshy drupaceous fruits attractive to frugivores. Figs, for example, are an important resource for many tropical vertebrates [68,69] including chimpanzees [40,70], due to their asynchronous fruiting. High densities of certain species (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation